Peroral endoscopic myotomy in a pediatric patient with refractory achalasia: a case report and review of the literature - Calixto-Aguilar, Lesly (2021)
A 15-year-old male patient presented with dysphagia, regurgitation, weight loss and retrosternal pain. The diagnosis of achalasia was made 4 years before. The esophagogram revealed severe esophagus dilatation and the classic “bird-beak” termination. A Heller myotomy plus fundoplication and endoscopic balloon dilatation were conducted four months previously. Nevertheless, the symptoms persisted and the last high-resolution manometry study still showed achalasia type II. The patient underwent a peroral endoscopic esophageal myotomy (POEM). POEM is a feasible and safe procedure for experienced and properly- equipped health care delivery centers and could be used as a rescue treatment in refr e present the youngest patient with achalasia in our region who had a successful response to rescue POEM.